Special water-based adhesive for bonding ship floor and preparation method of special water-based adhesive
By developing a water-based adhesive for boat floor bonding composed of water-based polyurethane, acrylic emulsion, viscosity-enhancing emulsion, modified asbestos powder, nanocarbon and doped polyaniline, the problem of poor adhesive stability in harsh environments is solved. It achieves high stability, corrosion resistance and water resistance, significantly improving the service life and construction efficiency of the glue.
Patent Information
- Application Number
- CN202510032137.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The adhesive is poor in the current harsh environment, which is difficult to meet the long-term use requirements of boat floors in high humidity and high temperature environments.
Provided is a water-based glue for boat floor bonding, which consists of component A and component B. Component A contains aqueous polyurethane, aqueous acrylic emulsion, aqueous viscosity enhancing emulsion, modified asbestos powder, nanocarbon and doping Polyaniline, component B is a water-dispersed polyisocyanate.
This water-based glue has high stability, high corrosion resistance and high water resistance, which can significantly improve the service life and water resistance of the glue, reduce construction time, and show excellent performance in high and low temperature aging tests.
Smart Images

Figure CN119410323A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of boat floor bonding, and in particular to a special water-based adhesive for boat floor bonding and a preparation method thereof. Background Art
[0002] As part of the interior materials, floor cloth is often used in various types of boats. In order to have better decorative properties and good sealing performance, the floor cloth is usually bonded to the floor with adhesive. The materials involved in the floor decoration in boats can be divided into two parts. One is the floor base, which is mainly aluminum honeycomb, stainless steel, and glued wood flooring; the other is the floor cloth, which is mainly synthetic rubber and composite PVC. Different materials require different adhesives, and the corresponding construction processes will also be very different.
[0003] Boat floor bonding is an important part of shipbuilding and maintenance, and appropriate adhesives and processes need to be selected to ensure the strength and durability of the bonding.
[0004] Adhesive selection: Commonly used adhesives for boat floor bonding include polyurethane glue, etc. These adhesives have good bonding strength, water resistance and weather resistance, and can meet the use requirements of boat floors in harsh environments.
[0005] Bonding process: When bonding the boat floor, you need to clean the floor surface first to ensure that there is no oil, dust or other impurities. Then, apply the adhesive evenly on the floor surface, paying attention to controlling the amount of adhesive to avoid too much or too little. Finally, bond the floors together according to the design requirements and use tools such as clamps to fix them to ensure a firm bond. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of poor stability of adhesives in harsh environments, and to provide a special water-based adhesive for bonding boat floors with high stability, high corrosion resistance and high water resistance and a preparation method thereof.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a special water-based adhesive for bonding boat floors, the special water-based adhesive for bonding boat floors comprises component A and component B, and the content ratio of the component A to the component B is 100:5~100:20; The component A comprises the following components in parts by weight: 40-60 wt% of aqueous polyurethane, 20-30 wt% of aqueous acrylic emulsion, 5-15 wt% of aqueous thickening emulsion, 5-8 wt% of modified asbestos powder, 5-8 wt% of nano-carbon, 5-8 wt% of doped polyaniline, 0.2-0.4 wt% of indicator, and 1-2 wt% of auxiliary agent; The component B is a water-dispersible polyisocyanate.
[0008] The second aspect of the present invention provides a method for preparing the special water-based adhesive for bonding boat floors according to the first aspect of the present invention, the method comprising the following steps: (1) Weighing waterborne polyurethane and waterborne acrylic emulsion according to weight ratio, performing a first stirring, and obtaining a mixed solution I; (2) weighing an aqueous thickening emulsion according to the weight ratio and adding it to the mixed solution I for a second stirring to obtain a mixed solution II; (3) Weighing modified asbestos powder, nanocarbon, and doped polyaniline according to weight ratio and adding them to the mixed solution II for a third stirring to obtain a mixed solution III; (4) weighing an indicator according to the weight ratio and adding it to the mixed solution III for a fourth stirring to obtain a mixed solution IV; (5) Weighing an auxiliary agent according to the weight ratio and adding it to the mixed solution IV for a fifth stirring to obtain component A; (6) The viscosity of component A is adjusted to 8000-12000 mPa•s with the thickener, and then the component A is inspected, filtered, weighed, packaged, and stored. When it is used, component B is added and mixed; the dosage ratio of component A to component B is 100:5-100:20.
[0009] The third aspect of the present invention provides a special water-based adhesive for bonding boat floors prepared by the method described in the second aspect of the present invention.
[0010] The special water-based adhesive for bonding boat floors and the preparation method thereof provided by the present invention also have at least the following beneficial effects: (1) The water-based adhesive for bonding boat floors provided by the present invention is solvent-free, low in odor, low in VOC, and does not contain antioxidants, anti-aging agents, metal oxides and other ingredients. It has moderate and adjustable viscosity and can be applied by brushing, scraping or spraying. It has high initial adhesion and can be moved after heating for 3-5 minutes without affecting subsequent construction operations, which can greatly save the overall installation time. (2) The high molecular weight doped polyaniline in the water-based adhesive for bonding boat floors provided by the present invention has a redox dual structure, which can catalyze the formation of a dense passivation film on the surface of steel, iron, aluminum and other structures, thereby protecting the steel from corrosion, greatly improving the anti-corrosion performance of the adhesive, and greatly increasing the service life of the adhesive; (3) The modified asbestos and nano-carbon in the water-based adhesive for bonding boat floors provided by the present invention can effectively reduce the damage of water molecules to the adhesive, solve the defects of the obtained water-based adhesive such as poor water resistance and poor blister resistance, and significantly improve the water resistance and usage scenarios of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1is a graph of the number average molecular weight of doped polyaniline 1 in an embodiment of the present invention; Figure 2 is a graph of the number average molecular weight of doped polyaniline II in an embodiment of the present invention; Figure 3 is a graph of the number average molecular weight of doped polyaniline III in an embodiment of the present invention; Figure 4 is a graph of the number average molecular weight of doped polyaniline tetramer according to an embodiment of the present invention; Figure 5 It is a linear function standard curve with "elution time of PMMA1~PMMA10" as the horizontal axis and "response intensity / molecular weight" as the vertical axis. DETAILED DESCRIPTION
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0013] In the present invention, PMMA means polymethyl methacrylate.
[0014] In the present invention, the "based on PMMA" in "in the component A, the doped polyaniline is hydrochloric acid doped polyaniline, based on PMMA, the weight average molecular weight of the hydrochloric acid doped polyaniline is 120000-160010, and the number average molecular weight is 50000-75000" is because: in the process of detecting the molecular weight of hydrochloric acid doped polyaniline, PMMA is used as a standard, specifically, the relative molecular weights of 1214000, 28000, 611000, 12970, 3260 00, 6030, 219000, 1260, 56500, and 580 of PMMA1~PMMA10, and the standard curves of PMMA1~PMMA10 were obtained respectively, and the elution time of PMMA1~PMMA10 was obtained respectively, and then the above-mentioned "elution time" was used as the horizontal coordinate and the "response intensity / molecular weight" was used as the vertical coordinate to obtain a linear function standard curve, and then the "retention time" of the doped polyaniline with the molecular weight to be detected was substituted into the obtained linear function standard curve to obtain the molecular weight of the doped polyaniline.
[0015] As mentioned above, the first aspect of the present invention provides a special water-based adhesive for bonding boat floors, the special water-based adhesive for bonding boat floors comprises component A and component B, and the content ratio of component A to component B is 100:5~100:20; The component A comprises the following components in parts by weight: 40-60 wt% of aqueous polyurethane, 20-30 wt% of aqueous acrylic emulsion, 5-15 wt% of aqueous thickening emulsion, 5-8 wt% of modified asbestos powder, 5-8 wt% of nano-carbon, 5-8 wt% of doped polyaniline, 0.2-0.4 wt% of indicator, and 1-2 wt% of auxiliary agent; The component B is a water-dispersible polyisocyanate; In the component A, the doped polyaniline is hydrochloric acid doped polyaniline, based on PMMA, and the weight average molecular weight of the hydrochloric acid doped polyaniline is 120000-160010, and the number average molecular weight is 50000-75000.
[0016] In the present invention, the waterborne polyurethane is a heat-activated two-component waterborne polyurethane, which has good bonding properties to aluminum honeycomb, PVC, rubber floor cloth, and metal, and its 90-degree bonding strength is greater than 2N / mm (aluminum plate-PVC floor), and can effectively improve the low temperature resistance, high temperature and high humidity resistance of the formula.
[0017] In the present invention, the water-based acrylic emulsion has good water resistance, low VOC, and strong bonding strength to aluminum and plywood floors. After bonding (aluminum plate-PVC floor), the 90-degree peeling strength after being soaked in water at room temperature for seven days is still greater than 2N / mm.
[0018] In the present invention, the aqueous tackifying emulsion is a modified rosin polyester, which can significantly improve the initial viscosity, holding force, and peel strength of the formula, and make the formula reach the optimal balance point. The type and optimal amount of the tackifying resin should be selected from six aspects, namely, compatibility with the rubber elastomer, color, tackifying effect, aging resistance, and price.
[0019] In the present invention, the modified asbestos powder can significantly improve the water resistance of the formula. The screening method of the modified asbestos powder is as follows: the asbestos powder is modified by using a silane coupling agent, and the key is to expose its outer silicate layer so as to react with the silanol group after hydrolysis of the silane coupling agent.
[0020] In the present invention, nanocarbon has the characteristics of high adsorption, high activation, good dispersibility and good conductivity, and can significantly improve the water resistance and anti-corrosion performance of the formula. The screening method of the nanocarbon is that the nanocarbon particles generate hydrogen bonds through the surface silanol groups to form a silicon dioxide aggregate network, thereby enhancing the bonding force of the glue.
[0021] In the present invention, doped polyaniline can significantly improve the anti-corrosion performance of the formula. The doped polyaniline screening method is hydrochloric acid doped polyaniline, based on PMMA, with a weight average molecular weight greater than 100,000, a number average molecular weight greater than 40,000, and a doping rate of hydrochloric acid of 8%, which can effectively enhance the anti-corrosion performance of the glue.
[0022] In the present invention, the blue color paste is used as an indicator, and its function is to judge the thickness of the coating glue according to the color during use.
[0023] In the present invention, the mildewproofing agent, preservative, defoaming agent, wetting agent and thickening agent are auxiliary agents, which can effectively improve the storage stability of the product, improve the glue coating construction efficiency and the application stability of the final product.
[0024] Preferably, in the component A, the solid content of the waterborne polyurethane is 50±1wt%, the pH is 6.0-9.0, the minimum thermal activation temperature is 55-60°C, and the minimum film-forming temperature is <5°C.
[0025] Further preferably, in the component A, the solid content of the aqueous acrylic emulsion is 52±2wt%, the pH is 5.0-7.0, the viscosity is 3000-10000cps, and the 180° peel strength on the aluminum-canvas substrate is >5N / mm.
[0026] Preferably, in the component A, the solid content of the aqueous thickening emulsion is 54-56 wt %, the pH value is 7-9, and the Brookfield viscosity at 63#, 60 rpm, and 25° C. is ≤300 mPaS.
[0027] Preferably, in the component A, in the aqueous viscosity-enhancing emulsion, the average particle size of the dropping point is ≤600nm, and the softening point of the dropping point is 95-105°C.
[0028] Preferably, in the component A, the modified asbestos powder has a purity of ≥90%, an adsorption rate of 80-90%, and a density of 1.6-2.2 g / ml.
[0029] Further preferably, in the component A, the average particle size of the nanocarbon is 20-25 nm.
[0030] More preferably, in the component A, the doping rate of hydrochloric acid in the hydrochloric acid-doped polyaniline is 8 wt % based on PMMA.
[0031] According to a particularly preferred embodiment, in the component A, the preparation method of the hydrochloric acid-doped polyaniline is as follows: 186.25 g of aniline was weighed, added to 2 mol / L hydrochloric acid, transferred to an ice water bath and stirred for 20 minutes to obtain an aniline-hydrochloric acid solution, when the reaction temperature was 3-5° C., a 25 wt % hydrogen peroxide solution was added dropwise, and the dropwise addition was stopped after 20 minutes. The reaction was carried out at a reaction temperature of 3-5° C. for 2 hours, filtered, and a solid residue was obtained by filtration, and washed with distilled water until the pH value of the filtrate was 6.0-6.5 to obtain the hydrochloric acid-doped polyaniline; the molar ratio of the aniline to the hydrochloric acid was 1:1; and the dropping speed of the hydrogen peroxide solution was one drop per 2-3 seconds.
[0032] Preferably, in the component A, the indicator is a blue color paste.
[0033] Preferably, in the component A, the auxiliary agents include mildew inhibitors, preservatives, defoaming agents, wetting agents, and thickeners.
[0034] Preferably, in the component B, the polyisocyanate is selected from at least one of hydrophilically modified hexamethylene diisocyanate, hydrophilically modified isophorone diisocyanate, and hydrophilically modified diphenylmethane diisocyanate.
[0035] As mentioned above, the second aspect of the present invention provides a method for preparing the special water-based adhesive for bonding boat floors according to the first aspect of the present invention, the method comprising the following steps: (1) Weighing waterborne polyurethane and waterborne acrylic emulsion according to weight ratio, performing a first stirring, and obtaining a mixed solution I; (2) weighing an aqueous thickening emulsion according to the weight ratio and adding it to the mixed solution I for a second stirring to obtain a mixed solution II; (3) Weighing modified asbestos powder, nanocarbon, and doped polyaniline according to weight ratio and adding them to the mixed solution II for a third stirring to obtain a mixed solution III; (4) weighing an indicator according to the weight ratio and adding it to the mixed solution III for a fourth stirring to obtain a mixed solution IV; (5) Weighing an auxiliary agent according to the weight ratio and adding it to the mixed solution IV for a fifth stirring to obtain component A; (6) The viscosity of component A is adjusted to 8000-12000 mPa•s with the thickener, and then the component A is inspected, filtered, weighed, packaged, and stored. When it is used, component B is added and mixed; the dosage ratio of component A to component B is 100:5-100:20.
[0036] Preferably, in step (1), the first stirring conditions are: a stirring speed of 300-500 r / min, and a stirring time of 10-15 min.
[0037] Further preferably, in step (2), the second stirring conditions are: a stirring speed of 500-800 r / min, and a stirring time of 10-25 min.
[0038] Preferably, in step (3), the third stirring conditions are: a stirring speed of 500-800 r / min, and a stirring time of 10-25 min.
[0039] More preferably, in step (4), the fourth stirring conditions are: a stirring speed of 800-1200 r / min, and a stirring time of 20-30 min.
[0040] Preferably, in step (5), the fifth stirring conditions are: a stirring speed of 300-500 r / min, and a stirring time of 5-10 min.
[0041] Preferably, in step (6), the sixth stirring conditions are: a stirring speed of 500-700 r / min, and a stirring time of 10-15 min.
[0042] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.
[0043] In the following examples, unless otherwise specified, doped polyaniline 1: hydrochloric acid doped polyaniline, based on PMMA, has a weight average molecular weight of 145597 and a number average molecular weight of 67580 (e.g. Figure 1 As shown in Table 1), the doping rate of hydrochloric acid is 8wt%; Doped polyaniline 2: hydrochloric acid doped polyaniline, based on PMMA, has a weight average molecular weight of 160010 and a number average molecular weight of 73884 (such as Figure 2 As shown in Table 2), the doping rate of hydrochloric acid is 8wt%; Doped polyaniline 3: hydrochloric acid doped polyaniline, based on PMMA, has a weight average molecular weight of 129320 and a number average molecular weight of 57259 (such as Figure 3 As shown in Table 3), the doping rate of hydrochloric acid is 8wt%; Doped polyaniline 4: Sulfuric acid doped polyaniline, based on PMMA, has a weight average molecular weight of 9653 and a number average molecular weight of 4149 (e.g. Figure 4 As shown in Table 4), the doping rate of sulfuric acid is 8wt%; The reason for “taking PMMA as the benchmark” is that: in the process of detecting the molecular weight of hydrochloric acid-doped polyaniline, PMMA is used as the standard. Specifically, PMMA1 to PMMA10 with relative molecular weights of 1214000, 28000, 611000, 12970, 326000, 6030, 219000, 1260, 56500, and 580 are used to obtain the standard curves of PMMA1 to PMMA10, and the elution time of PMMA1 to PMMA10 is obtained, respectively. Then, the above-mentioned “elution time” is used as the horizontal coordinate and “response intensity / molecular weight” is used as the vertical coordinate to obtain the linear function standard curve (such as Figure 5 As shown in FIG. 1 ), the “retention time” of the doped polyaniline of the molecular weight to be detected is then substituted into the obtained linear function standard curve to obtain the molecular weight of the doped polyaniline.
[0044] In the following examples, unless otherwise specified, the waterborne polyurethane has a solid content of 50-51 wt%, a pH of 6.0-9.0, a minimum thermal activation temperature of 60°C, and a minimum film-forming temperature of <5°C, and is purchased from Bayer AG of Germany, with the brand name of waterborne polyurethane U54; The water-based acrylic emulsion has a solid content of 49-51 wt%, a pH of 6.0-9.0, a viscosity of 1500-2000 cps, and a 180° peel strength of >5 N / cm on an aluminum-canvas substrate. It is purchased from Allnex and has a brand name of VISCOPOL 9250. The solid content of the aqueous thickening emulsion is 54-56wt%, the pH value is 7-9, the Brookfield viscosity at 63#, 60rpm, and 25°C is ≤300 mPaS, the average particle size at the dropping point is 600nm, and the softening point at the dropping point is 105°C. It is purchased from Wistar Company and the brand is AT100Y; The modified asbestos powder has a purity of 90%, an adsorption rate of 80%, and a density of 1.6-2.2 g / ml. It was purchased from Hengyue Minerals Company and has a brand name of A4-20. Nanocarbon, with an average particle size of 20 nm, was purchased from Suzhou Tanfeng Technology Co., Ltd., with the brand name TF-71001; Blue color paste, purchased from Shenzhen Xuancai Chemical Pigment Co., Ltd., brand C011; Antifungal agent, purchased from Shandong Wanhua Tianhe New Materials Co., Ltd., brand name: Kasong Antifungal Agent CA-05; Preservatives were purchased from Shenzhen Lvtai Environmental Protection Technology Co., Ltd., brand PGH-455; Defoaming agent, purchased from German company Tego, brand name Tego902w; Wetting agent, purchased from German company Tego, brand name Tego270; Thickener, purchased from Dow Chemical Company, brand RM2020; ; In Table 1, "Daltons" is a unit, which can be translated as Dalton; "Mz / Mw" means Z average molecular weight / weight average molecular weight; "Mz+1 / Mw" means Z+1 average molecular weight / weight average molecular weight; ; In Table 2, "Daltons" is a unit, which can be translated as Dalton; "Mz / Mw" means Z average molecular weight / weight average molecular weight; "Mz+1 / Mw" means Z+1 average molecular weight / weight average molecular weight; ; In Table 3, "Daltons" is a unit, which can be translated as Dalton; "Mz / Mw" means Z average molecular weight / weight average molecular weight; "Mz+1 / Mw" means Z+1 average molecular weight / weight average molecular weight; ; In Table 4, "Daltons" is a unit, which can be translated as Dalton; "Mz / Mw" represents Z average molecular weight / weight average molecular weight; and "Mz+1 / Mw" represents Z+1 average molecular weight / weight average molecular weight.
[0045] Embodiment 1: This example is used to provide a method for preparing a special water-based adhesive for bonding boat floors, the method comprising the following steps: (1) Weigh 48 kg of waterborne polyurethane and 23 kg of waterborne acrylic emulsion, add them into a stirring tank, and stir and disperse them at a speed of 500 r / min for 10 min to obtain a uniformly dispersed mixed solution I; (2) adding 8 kg of aqueous thickening emulsion to the mixed solution I, stirring at room temperature and a rotation speed of 500 r / min for 15 min to obtain a uniformly dispersed mixed solution II; (3) adding 6 kg of modified asbestos powder, 6 kg of nanocarbon and 7 kg of doped polyaniline to the mixed solution II, stirring at room temperature and a rotation speed of 500 r / min for 15 min to obtain a uniformly dispersed mixed solution III; (4) adding 0.3 kg of blue color paste to the mixed solution III, stirring at a speed of 800 r / min for 20 min to obtain a uniformly dispersed mixed solution IV; (5) adding 0.01 kg of mildew preventive, 0.01 kg of preservative, 0.01 kg of defoaming agent, 0.1 kg of wetting agent and 0.5 kg of thickener to the mixed solution IV, stirring at a speed of 500 r / min for 5 min to obtain component A; (6) Using a thickener to adjust the viscosity of component A to 8000-12000 mPa•s, inspect, filter, weigh, package, and store, and then add component B to mix when it is used; the dosage ratio of component A to component B is 100:6.
[0046] Wherein, the method for preparing the doped polyaniline comprises the following steps: 186.25 g of aniline was weighed, added to 2 mol / L hydrochloric acid, transferred to an ice water bath and stirred for dissolution for 20 minutes to obtain an aniline-hydrochloric acid solution, when the reaction temperature was 3-5° C., a 25 wt % hydrogen peroxide solution was added dropwise, and the dropwise addition was stopped after 20 minutes. The reaction was carried out at a reaction temperature of 3-5° C. for 2 hours, filtered, and a solid residue was obtained by filtration, and washed with distilled water until the pH value of the filtrate was 6.0-6.5 to obtain the hydrochloric acid-doped polyaniline; the molar ratio of the aniline to the hydrochloric acid was 1:1; and the dropping speed of the hydrogen peroxide solution was one drop every 2-3 seconds.
[0047] Embodiment 2: This example is used to provide a method for preparing a special water-based adhesive for bonding boat floors, the method comprising the following steps: (1) Weigh 45 kg of waterborne polyurethane and 20 kg of waterborne acrylic emulsion, add them into a stirring tank, and stir and disperse them at a speed of 500 r / min for 10 min to obtain a uniformly dispersed mixed solution I; (2) adding 15 kg of aqueous thickening emulsion to the mixed solution I, stirring for 15 min at room temperature and a rotation speed of 500 r / min to obtain a uniformly dispersed mixed solution II; (3) adding 5 kg of modified asbestos powder, 7 kg of nanocarbon and 5 kg of doped polyaniline to the mixed solution II, stirring at room temperature and a rotation speed of 500 r / min for 15 min to obtain a uniformly dispersed mixed solution III; (4) adding 0.5 kg of blue color paste to the mixed solution III, stirring at a speed of 800 r / min for 20 min to obtain a uniformly dispersed mixed solution IV; (5) adding 0.02 kg of mildew preventive, 0.02 kg of preservative, 0.01 kg of defoaming agent, 0.2 kg of wetting agent and 0.6 kg of thickener to the mixed solution IV, stirring at a speed of 500 r / min for 5 min, to obtain component A; (6) The viscosity of component A is adjusted to 8000-12000 mPa•s with the thickener, and then the component A is inspected, filtered, weighed, packaged, and stored. When it is used, component B is added and mixed; the dosage ratio of component A to component B is 100:15.
[0048] Wherein, the method for preparing the doped polyaniline comprises the following steps: 186.25 g of aniline was weighed, added to 2 mol / L hydrochloric acid, transferred to an ice water bath and stirred for dissolution for 20 minutes to obtain an aniline-hydrochloric acid solution, when the reaction temperature was 3-5° C., a 25 wt % hydrogen peroxide solution was added dropwise, and the dropwise addition was stopped after 20 minutes. The reaction was carried out at a reaction temperature of 3-5° C. for 2 hours, filtered, and a solid residue was obtained by filtration, and washed with distilled water until the pH value of the filtrate was 6.0-6.5 to obtain the hydrochloric acid-doped polyaniline; the molar ratio of the aniline to the hydrochloric acid was 1:1; and the dropping speed of the hydrogen peroxide solution was one drop every 2-3 seconds.
[0049] Embodiment 3: This example is used to provide a method for preparing a special water-based adhesive for bonding boat floors, the method comprising the following steps: (1) Weigh 50 kg of waterborne polyurethane and 25 kg of waterborne acrylic emulsion, add them into a stirring tank, and stir and disperse them at a speed of 500 r / min for 10 min to obtain a uniformly dispersed mixed solution I; (2) adding 5 kg of aqueous thickening emulsion to the mixed solution I, stirring at room temperature and a rotation speed of 500 r / min for 15 min to obtain a uniformly dispersed mixed solution II; (3) adding 7 kg of modified asbestos powder, 5 kg of nanocarbon and 8 kg of doped polyaniline to the mixed solution II, stirring at room temperature and a rotation speed of 500 r / min for 15 min to obtain a uniformly dispersed mixed solution III; (4) adding 0.2 kg of blue color paste to the mixed solution III, stirring at a speed of 800 r / min for 20 min to obtain a uniformly dispersed mixed solution IV; (5) adding 0.01 kg of mildew preventive, 0.02 kg of preservative, 0.02 kg of defoaming agent, 0.15 kg of wetting agent and 0.45 kg of thickener to the mixed solution IV, stirring at a speed of 500 r / min for 5 min, to obtain component A; (6) The viscosity of component A is adjusted to 8000-12000 mPa•s with the thickener, and then the component A is inspected, filtered, weighed, packaged, and stored. When it is used, component B is added and mixed; the dosage ratio of component A to component B is 100:20.
[0050] Wherein, the method for preparing the doped polyaniline comprises the following steps: 186.25 g of aniline was weighed, added to 2 mol / L hydrochloric acid, transferred to an ice water bath and stirred for dissolution for 20 minutes to obtain an aniline-hydrochloric acid solution, when the reaction temperature was 3-5° C., a 25 wt % hydrogen peroxide solution was added dropwise, and the dropwise addition was stopped after 20 minutes. The reaction was carried out at a reaction temperature of 3-5° C. for 2 hours, filtered, and a solid residue was obtained by filtration, and washed with distilled water until the pH value of the filtrate was 6.0-6.5 to obtain the hydrochloric acid-doped polyaniline; the molar ratio of the aniline to the hydrochloric acid was 1:1; and the dropping speed of the hydrogen peroxide solution was one drop every 2-3 seconds.
[0051] Embodiment 4: This example is carried out according to the method of Example 1, except that in step (3), the doped polyaniline 2 is used in the same amount to replace the doped polyaniline 1, and the remaining steps and parameters are the same as those of Example 1.
[0052] Wherein, the preparation method of the doped polyaniline II is as follows: 186.25 g of aniline was weighed, added to 1.5 mol / L hydrochloric acid, transferred to an ice water bath and stirred for dissolution for 20 min to obtain an aniline-hydrochloric acid solution, when the reaction temperature was 3-5° C., a 20 wt % hydrogen peroxide solution was added dropwise, and the dropwise addition was stopped after 20 min. The reaction was carried out at a reaction temperature of 3-5° C. for 2 h, and filtered to obtain a solid residue, which was rinsed with distilled water until the pH value of the filtrate was 6.0-6.5 to obtain the hydrochloric acid-doped polyaniline; the molar ratio of the aniline to the hydrochloric acid was 1:1; and the dropping speed of the hydrogen peroxide solution was one drop every 2-3 s.
[0053] Embodiment 5: This example is carried out according to the method of Example 1, except that in step (3), the doped polyaniline 3 is used in the same amount to replace the doped polyaniline 1, and the remaining steps and parameters are the same as those of Example 1.
[0054] Wherein, the preparation method of the doped polyaniline is as follows: 186.25 g of aniline was weighed, added to 2 mol / L hydrochloric acid, transferred to an ice water bath and stirred for dissolution for 20 minutes to obtain an aniline-hydrochloric acid solution, when the reaction temperature was 3-5° C., a 25 wt % hydrogen peroxide solution was added dropwise, and the dropwise addition was stopped after 20 minutes. The reaction was carried out at a reaction temperature of 3-5° C. for 2 hours, filtered, and a solid residue was obtained by filtration, and washed with distilled water until the pH value of the filtrate was 6.0-6.5 to obtain the hydrochloric acid-doped polyaniline; the molar ratio of the aniline to the hydrochloric acid was 1:1; and the dropping speed of the hydrogen peroxide solution was one drop every 2-3 seconds.
[0055] Comparative Example 1: The method of Example 1 is followed, except that in step (3), the same amount of doped polyaniline 4 is used to replace the doped polyaniline 1; in step (4), the amount of the blue color paste is 0.2 kg, and the stirring speed is 1000 r / min; in step (5), the amount of the mildew inhibitor is 0.05 kg, the amount of the preservative is 0.04 kg, the amount of the defoamer is 0.03 kg, the amount of the wetting agent is 0.3 kg, and the amount of the thickener is 0.3 kg; the stirring speed is 400 r / min, and the stirring time is 10 min. The remaining steps and parameters are the same as those of Example 1; Wherein, the method for preparing the doped polyaniline tetrazolium comprises the following steps: 186.25 g of aniline was weighed, added to sulfuric acid with a concentration of 2 mol / L, and transferred to an ice water bath and stirred for dissolution for 20 minutes to obtain an aniline-sulfuric acid solution. When the reaction temperature was 3-5° C., a 25 wt % hydrogen peroxide solution was added dropwise, and the dropwise addition was stopped after 20 minutes. The reaction was carried out at a reaction temperature of 3-5° C. for 2 hours, and the solid residue was filtered to obtain a solid residue, which was washed with distilled water until the pH value of the filtrate was 6.0-6.5 to obtain the sulfuric acid-doped polyaniline. The molar ratio of the aniline to the sulfuric acid was 1:1. The dropwise addition speed of the hydrogen peroxide solution was one drop every 2-3 seconds.
[0056] Comparative Example 2: This example is carried out according to the method of Example 1, except that in step (3), the doped polyaniline 5 is used in the same amount to replace the doped polyaniline 1, and the remaining steps and parameters are the same as those of Example 1; Wherein, in the hydrochloric acid-doped polyaniline 5, based on PMMA, the doping rate of hydrochloric acid is 10wt%, and the remaining steps and parameters are the same as those in Preparation Example 1.
[0057] Comparative Example 3: This example is carried out according to the method of Example 1, except that in step (6), component B is added during the production process instead of during use. The remaining steps and parameters are the same as in Example 1.
[0058] Test example: The special water-based adhesive for bonding boat floors obtained in the above examples and comparative examples was tested, and the results are shown in Tables 5 and 6; ; In Table 5, "curing time" means the time it takes to walk on the floor after paving and proceed to the next process; "180° peel strength" means the test on the aluminum-rubber floor cloth; "water resistance" means the strength retention rate is ≥75% after soaking in 50℃ hot water for at least 168h or in room temperature water for 168h; "high and low temperature 90° peel strength" means the high and low temperature is 70℃~-40℃ / 5 cycles: ; In Table 6, "curing time" means the time it takes to walk on the floor after paving and proceed to the next process; "180° peel strength" means the test on the aluminum-rubber floor cloth; "water resistance" means the strength retention rate is ≥75% after soaking in 50°C hot water for at least 168h or in room temperature water for 168h; "high and low temperature 90° peel strength" means the high and low temperature is 70°C~-40°C / 5 cycles.
[0059] It can be seen from the results of Table 5 and Table 6 that the special water-based adhesive for bonding boat floors prepared by the embodiment of the present invention has significantly better peel strength, corrosion resistance and water resistance, and its advantages are more obvious in the aging high and low temperature test.
[0060] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A special water-based adhesive for bonding boat floors, characterized in that: The special water-based adhesive for bonding boat floors comprises component A and component B, and the content ratio of component A to component B is 100:5-100:20; The component A comprises the following components in parts by weight: 40-60 wt% of aqueous polyurethane, 20-30 wt% of aqueous acrylic emulsion, 5-15 wt% of aqueous thickening emulsion, 5-8 wt% of modified asbestos powder, 5-8 wt% of nano-carbon, 5-8 wt% of doped polyaniline, 0.2-0.4 wt% of indicator, and 1-2 wt% of auxiliary agent; The component B is a water-dispersible polyisocyanate; In the component A, the doped polyaniline is hydrochloric acid doped polyaniline. Based on PMMA, the weight average molecular weight of the hydrochloric acid doped polyaniline is 120000-160010, and the number average molecular weight is 50000-75000.
2. The special water-based adhesive for bonding boat floors according to claim 1, characterized in that: In the component A, the solid content of the waterborne polyurethane is 50±1wt%, the pH is 6.0-9.0, the minimum thermal activation temperature is 55-60°C, and the minimum film-forming temperature is <5°C.
3. The special water-based adhesive for bonding boat floors according to claim 1 or 2, characterized in that: In the component A, the solid content of the aqueous acrylic emulsion is 52±2wt%, the pH is 5.0-7.0, the viscosity is 3000-10000cps, and the 180° peel strength on the aluminum-canvas substrate is >5N / mm.
4. The special water-based adhesive for bonding boat floors according to claim 1 or 2, characterized in that: In the component A, the solid content of the aqueous thickening emulsion is 54-56wt%, the pH value is 7-9, and the Brookfield viscosity at 63#, 60rpm, and 25°C is ≤300 mPaS; And or, in the component A, in the aqueous thickening emulsion, the average particle size of the dropping point is ≤600nm, and the softening point of the dropping point is 95~105℃.
5. The special water-based adhesive for bonding boat floors according to claim 1 or 2, characterized in that: In the component A, the modified asbestos powder has a purity of ≥90%, an adsorption rate of 80-90%, and a density of 1.6-2.2 g / ml; And / or, in the component A, the average particle size of the nanocarbon is 20-25 nm.
6. The special water-based adhesive for bonding boat floors according to claim 1 or 2, characterized in that: In the component A, the doping rate of hydrochloric acid in the hydrochloric acid-doped polyaniline is 8wt%; And / or, in the component A, the preparation method of the hydrochloric acid-doped polyaniline is as follows: Weigh 186.25g of aniline, add it to hydrochloric acid with a concentration of 2mol / L, transfer it to an ice water bath and stir and dissolve it for 20min to obtain an aniline-hydrochloric acid solution, when the reaction temperature is 3-5°C, add a 25wt% hydrogen peroxide solution dropwise, stop dropping after 20min, react at a reaction temperature of 3-5°C for 2h, filter, filter to obtain a solid residue, rinse with distilled water until the pH value of the filtrate is 6.0-6.5, and obtain the hydrochloric acid-doped polyaniline; the molar ratio of the aniline to the hydrochloric acid is 1:1; the dropping speed of the hydrogen peroxide solution is one drop per 2-3s; And / or, in the component A, the indicator is a blue color paste; And / or, in the component A, the auxiliary agent includes a mildew preventer, a preservative, a defoaming agent, a wetting agent, and a thickener.
7. The special water-based adhesive for bonding boat floors according to claim 1 or 2, characterized in that: In the component B, the polyisocyanate is selected from at least one of hydrophilically modified hexamethylene diisocyanate, hydrophilically modified isophorone diisocyanate, and hydrophilically modified diphenylmethane diisocyanate.
8. A method for preparing the special water-based adhesive for bonding boat floors as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) Weighing waterborne polyurethane and waterborne acrylic emulsion according to weight ratio, performing a first stirring, and obtaining a mixed solution I; (2) weighing an aqueous thickening emulsion according to the weight ratio and adding it to the mixed solution I for a second stirring to obtain a mixed solution II; (3) Weighing modified asbestos powder, nanocarbon, and doped polyaniline according to weight ratio and adding them to the mixed solution II for a third stirring to obtain a mixed solution III; (4) weighing an indicator according to the weight ratio and adding it to the mixed solution III for a fourth stirring to obtain a mixed solution IV; (5) Weighing an auxiliary agent according to the weight ratio and adding it to the mixed solution IV for a fifth stirring to obtain component A; (6) The viscosity of component A is adjusted to 8000-12000 mPa•s with the thickener, and then the component A is inspected, filtered, weighed, packaged, and stored. When it is used, component B is added and mixed; the dosage ratio of component A to component B is 100:5-100:20.
Citation Information
Patent Citations
Boat water resistant adhesive
CN103045107A
Water-based two-component adhesive
CN112852375A
Marine nano polyaniline heavy anti-corrosion primer as well as preparation method and application thereof
CN118185417A
Urethane resin composition and heavy duty corrosion preventing coating material
JP1997194563A
Metal base material and heat exchanger using it
JP2005262769A